Social Actions: Making the Web More Philanthropic - Peter Deitz; Christine Egger (Open Source Business Resource, 2009)
Social Actions makes it easier for people to turn their good intentions into meaningful action. The organization has created an open source database of actions people can take on any issue. The actions in the database come from across the social web and include everything from volunteer opportunities to micro credit loans. It currently aggregates opportunities to make a difference from 50+ action sources, including: CanadaHelps, Kiva, Idealist, GlobalGiving, GiveIndia, and Greater Good South Africa. Using the Social Actions application programming interface, we encourage third party developers to build web and mobile applications that intelligently distribute actions from our database on the websites, social networks, and mobile phones that millions of people use every day. This article describes how Social Actions applies open source principles to the organization's products and processes. In its entirety, Social Actions is intentionally designed to contribute to the ongoing and vibrant conversations about open source practices and principles.